The Effect of a Liver Transplant Program on the Outcomes of Resectable Hepatocellular Carcinoma: A Nationwide Multicenter Analysis. Issue 4 (29th April 2023) - Serenari, Matteo; Lenzi, Jacopo; Cucchetti, Alessandro; Cipriani, Federica; Donadon, Matteo; Ardito, Francesco; Fazio, Federico; Nicolini, Daniele; Iaria, Maurizio; Famularo, Simone; Perri, Pasquale; Ansaloni, Luca; et al.
Abstract : Objective: To evaluate the effect of a liver transplantation (LT) program on the outcomes of resectable hepatocellular carcinoma (HCC). Background: Surgical treatment of HCC includes both hepatic resection (HR) and LT. However, the presence of cirrhosis and the possibility of recurrence make the management of this disease complex and probably different according to the presence of a LT program. Methods: Patients undergoing HR for HCC between January 2005 and December 2019 were identified from a national database of HCC. The main study outcomes were major surgical complications according to the Comprehensive Complication Index, posthepatectomy liver failure (PHLF), 90-day mortality, overall survival, and disease-free survival. Secondary outcomes were salvage liver transplantation (SLT) and postrecurrence survival. Results: A total of 3202 patients were included from 25 hospitals over the study period. Three of 25 (12%) had an LT program. The presence of an LT program within a center was associated with a reduced probability of PHLF (odds ratio=0.38) but not with overall survival and disease-free survival. There was an increased probability of SLT when HR was performed in a transplant hospital (odds ratio=12.05). Among transplant-eligible patients, those who underwent LT had a significantly longer postrecurrence survival. Conclusions: This study showed that the presence of a LT program was associated with decreased PHLF rates and an increased probability to receive SLT in case of recurrence.